1998
DOI: 10.1021/jp982627y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HNO3 and HCl on D2O Desorption Kinetics from Crystalline D2O Ice

Abstract: The presence of trace species may perturb H2O desorption kinetics from ice surfaces and alter the stability of atmospheric ice particles. To investigate the effects of atmospheric species on H2O desorption kinetics from crystalline ice, the D2O desorption kinetics from pure and HNO3- and HCl-dosed crystalline D2O ice multilayers on Ru(001) were investigated using isothermal laser-induced thermal desorption (LITD) measurements. The D2O desorption kinetics were studied for D2O ice film thicknesses of 25−200 BL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 96 publications
8
51
0
Order By: Relevance
“…These results are only in partial agreement with those of Livingston and George [28]. They found that exposing ice to HCl increases the activation barrier to ice desorption.…”
Section: Ice Ice Coated With Hcl and Nitric Acidsupporting
confidence: 70%
See 2 more Smart Citations
“…These results are only in partial agreement with those of Livingston and George [28]. They found that exposing ice to HCl increases the activation barrier to ice desorption.…”
Section: Ice Ice Coated With Hcl and Nitric Acidsupporting
confidence: 70%
“…Another difference between the two studies is the temperature range. In the present work, the evaporation experiments were done between 170 and 180 K, slightly higher than the previous work, though there is no sign between 150 and 171 K that there should be a strong temperaturedependence to the enhancement or hindrance of ice evaporation [28]. One other difference is in how the ice was prepared.…”
Section: Ice Ice Coated With Hcl and Nitric Acidmentioning
confidence: 60%
See 1 more Smart Citation
“…Our results can also be compared to very recent studies by Livingston and George [1998]. Livingston and George [1998] found that 0.3-3.0 bilayers of HNO3 adsorbed on thin ice films decreased ice evaporation rates by a factor of 3-5 over the temperature range 150-171 K. Based on our experiments, we believe this could only happen if a sealing layer formed over ice.…”
Section: Discussionsupporting
confidence: 82%
“…The evaporative lifetime of complex atmospheric ice particles is longer than hitherto believed owing to the slower than expected evaporation rate of H 2 O in the presence of HCl and HNO 3 (Livingston and George, 1998;Delval et al, 2003). The decrease of the absolute rate of H 2 O evaporation relative to pure H 2 O ice is a function of the amount of adsorbed trace gas and the structure of the trace gas hydrate being either in an amorphous or crystalline state.…”
Section: Trace Gas Uptake On Ice Surfacesmentioning
confidence: 93%